Вплив магнітно-вихревої обробки дизельного палива на процес сумішоутворення та горіння в дизельному двигуні - Савінов, В'ячеслав Петрович; Галько, Сергій Віталійович; Savinov, Viacheslav; Halko, Serhii (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Між електричними і магнітними полями існує глибокий внутрішній зв’язок. Будь-яка зміна магнітного поля завжди супроводжується появою електричного поля і навпаки. Електричне поле може створюватися не тільки зарядами, але і магнітним полем, джерелом якого є постійні магніти та електричні мікроструми, що циркулюють усередині молекул палива. У роботі досліджується вплив магніто-вихрової обробки дизельного палива на його фізичні характеристики та параметри процесу згоряння у двигуні. Експериментально показано, що проходження палива через систему послідовно встановлених постійних магнітів різних геометричних розмірів та магнітних характеристик призводить до зміни параметрів упорскування, кута випередження запалення та динаміки горіння. При цьому спостерігається зниження щільності палива, температури спалаху, зольного залишку, вмісту сірки, навантаження на мотор при збереженні потужності двигуна. Отримані результати інтерпретуються з позицій гідродинаміки, фазових ефектів та кінетики горіння. /// EN: By examining interaction processes in the material world through environmental energy and their influence on the internal molecular structure, new interpretations of natural phenomena can be developed. Electric charges arise when different substances come into close contact. In some materials, charges can move freely, whereas in others this is not possible. The interaction between bodies depends on their shape and relative position, while electric charges are distributed throughout their volume. A close relationship exists between electric and magnetic fields, manifested in their ability to transform into each other. Any change in a magnetic field induces an electric field, and conversely, a changing electric field generates a magnetic field. An electric field can be created not only by moving charges but also by a time-varying magnetic field. The sources of magnetic fields include permanent magnets and electric microcurrents circulating within fuel molecules. This study investigates the effect of magnetic vortex treatment of diesel fuel on its physical properties and combustion parameters in a diesel engine. It is experimentally shown that passing fuel through a system of sequentially arranged permanent magnets with different geometric dimensions and magnetic permeability characteristics, forming a vortex flow structure, leads to changes in injection parameters, ignition timing, combustion duration, and combustion dynamics. A decrease in fuel density, flash point, ash content, and sulfur concentration is observed. Modification of the energy and structural parameters of the fuel improves its homogeneity, increases the proportion of active fractions, and enhances evaporation and mixture formation conditions. This ensures more stable ignition and more complete combustion in internal combustion engine cylinders. The results confirm the potential of magnetic and electrophysical methods for modifying diesel fuel properties and improving combustion efficiency. Further studies should focus on expanding the experimental base and clarifying the physical mechanisms of magnetic field influence on hydrocarbon fuel molecules.
The influence of magnetic-vortex treatment of diesel fuel on the process of mixture formation and combustion in a diesel engine
Keywords: електричне поле; магнітне поле; електрофізична дія; магнітогідродинаміка; якість палива; electric field; magnetic field; electrophysical impact; magnetohydrodynamics; fuel quality